2012
DOI: 10.1063/1.4718450
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ca-deficiency on the magneto-transport properties in La0.8Ca0.2MnO3 perovskite and estimation of magnetic entropy change

Abstract: La 0.8 Ca 0.2 À x h x MnO 3 (x ¼ 0.00, 0.10, and 0.20) perovskite was prepared by the conventional solid-state reaction and annealed at 1473 K. X-ray diffraction and scanning electron microscopy shown the existence of a secondary phase attributed to the unreacted Mn 3 O 4 oxide. The magneto transport properties have been investigated based on the temperature dependence of the resistivity q(T) measurements under several applied magnetic fields. We note that the La 0.8 Ca 0.2 MnO 3 (x ¼ 0.00) sample has a classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…It is observed that as Ba-content increases, the metal insulator transition temperature T MI monotonically shifts towards higher temperature region. Pristine sample exhibits T MI around 210 K, which is matching with that reported in literature [13,28]. We now explain the reasons for the observed increase of T MI with Ba content.…”
Section: Resistivity and Magneto-resistancesupporting
confidence: 83%
See 1 more Smart Citation
“…It is observed that as Ba-content increases, the metal insulator transition temperature T MI monotonically shifts towards higher temperature region. Pristine sample exhibits T MI around 210 K, which is matching with that reported in literature [13,28]. We now explain the reasons for the observed increase of T MI with Ba content.…”
Section: Resistivity and Magneto-resistancesupporting
confidence: 83%
“…In particular La 1-x Ca x MnO 3 (LCMO) compounds have attracted extra attention because of occurrence of enormous magneto-resistance (MR) and huge magneto-caloric effect (MCE) which makes them good candidates for applications [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…GP in the case of La 1-x Ca x MnO 3 is believed to arise from the disorders arising from the tilting of MnO 6 octahedron [8,13] where as the static Jahn-Teller distortion leads to GP in La 1-x Sr x MnO 3 system [12]. Nevertheless, there are contradictory reports [14,15,16] on the existence of GP in La 0.8 Ca 0.2 MnO 3 system. Khlifi et al [14] and Zang et al [15] have observed the absence of GP in La 0.8 Ca 0.2 MnO 3 system whereas Fatnassi et al [16] have reported the presence of GP.…”
Section: Introductionmentioning
confidence: 94%
“…Khlifi et al [14] and Zang et al [15] have observed the absence of GP in La 0.8 Ca 0.2 MnO 3 system whereas Fatnassi et al [16] have reported the presence of GP. It may be mentioned that Khlifi et al [14] have reported introduction of GP when calcium deficiency is brought into La 0.8 Ca 0.2 MnO 3 system.…”
Section: Introductionmentioning
confidence: 95%
“…This makes them good candidates for a wide variety of applications. [4][5][6][7][8] As regards the La 1Àx Ca x MnO 3 compounds, they have a disadvantage that their Curie temperatures, T C , are well below room temperature. On the other side, doping Ca sites with large ions, for example Pb, Ba and Sr, has been explored by several researchers.…”
Section: Introductionmentioning
confidence: 99%